Who and What Do Who and What Range Over Cross-Linguistically?. (2nd June 2022) - Elliott, Patrick D; Nicolae, Andreea C; Sauerland, Uli
Abstract: Dayal's (1996) account of the presuppositions of wh- questions makes faulty predictions for languages which draw number distinctions in the domain of simplex wh- expressions: (Dayal, 1996 ) predicts that a singular wh- expression should always give rise to a Uniqueness Presupposition ; the Anti-Singleton Inference associated with its plural counterpart is expected to be parasitic on the uniqueness presupposition. Using data from Spanish, Greek, and Hungarian, where simplex wh- expressions inflect for number, we claim that singular simplex wh -expressions do not give rise to a Uniqueness Presupposition, but plural simplex wh -expressions nonetheless give rise to an Anti-Singleton Inference. We provide an analysis of these facts that is consistent with Dayal's (1996) account of constituent questions, by assigning simplex wh- expressions a type-ambiguous denotation.